1993
DOI: 10.1002/ijc.2910540411
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the target antigen for cytotoxic T lymphocytes on adult T‐cell‐leukemia cells

Abstract: Adult T-cell-leukemia (ATL) cells were examined for susceptibility to human T-cell-leukemia virus type I (HTLV-I) tax-specific cytotoxic T lymphocytes (CTL) derived from a patient with HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP). These CTL efficiently killed HLA-matched leukemia cells of an ATL patient after overnight incubation. However, ATL cells immediately after isolation from the peripheral blood were only marginally susceptible to the CTL. This is not due to inappropriate expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…36 As shown previously, significantly lower levels of HTLV-I tax mRNA were present in the fresh ATL cells than in the cultured ATL cells. 37 Moreover, the gene expression profile easily changed under the culture conditions in vitro. Therefore, our approach to examining primary ATL should provide valuable information on molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…36 As shown previously, significantly lower levels of HTLV-I tax mRNA were present in the fresh ATL cells than in the cultured ATL cells. 37 Moreover, the gene expression profile easily changed under the culture conditions in vitro. Therefore, our approach to examining primary ATL should provide valuable information on molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, since ATLL cells have been shown to constitutively produce cytokines with immunosuppressive properties such as TGF-b, 26 IL-10, 25 and VEGF, 27 their massive proliferation in vivo could strongly impair the processes of CD8 þ T-cell proliferation and differentiation. Reduced priming of CD8 þ T cells could also be related to mechanism of immune escape developed in ATLL cells such as extinction of Tax expression [28][29][30] and/or decreased recognition of Tax epitopes due to downregulation of MHC-I expression 31 or mutations into immunodominant Tax epitopes. 21 In conclusion, we demonstrated that the anti-HTLV-1 CD8 þ T-cell response found in ATLL patients differs from that of other HTLV-1-infected individuals because CD8 þ effectors are not generated or are not functional.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1 Taxspecific CTLs are capable of lysing short-term cultured ATL cells in vitro. 171 HTLV-1 Tax-specific CTLs might contribute to antitumor effects in HTLV-1 infected patients. In rat models, the antitumor effects was mediated by T-cells directed to HTLV-1 Tax.…”
Section: Vaccinationmentioning
confidence: 99%